The aqueous supramolecular chemistry of crown ethers - Qi, Zhenhui; Qin, Yao; Wang, Jijun; Zhao, Maojin; Yu, Zhuo; Xu, Qiangqiang; Nie, Hongqi; Yan, Qilong; Ge, Yan (Frontiers in Chemistry, 2023)
This mini-review summarizes the seminal exploration of aqueous supramolecular chemistry of crown ether macrocycles. In history, most research of crown ethers were focusing on their supramolecular chemistry in organic phase or in gas phase. In sharp contrast, the recent research evidently reveal that crown ethers are very suitable for studying abroad range of the properties and applications of water interactions, from: high water-solubility, control of Hofmeister series, “structural water”, and supramolecular adhesives. Key studies revealing more details about the properties of water and aqueous solutions are highlighted.